Exact Capacity Analysis of Multihop Transmission over Amplify-and-Forward Relay Fading Channels - Yilmaz, Ferkan; Kucur, Oğuz; Alouini, Mohamed-Slim (IEEE, 2010)
In this paper, we propose an analytical framework on the exact computation of the average capacity of multihop transmission over amplify-and-forward relay fading channels. Our approach relies on the algebraic combination of Mellin and Laplace transforms to obtain exact single integral expressions which can be easily computed by Gauss-Chebyshev Quadrature ( GCQ) rule. As such, the derived results are a convenient tool to analyze the average capacity of multihop transmission over amplify-and-forward relay fading channels. As an application of the analytical framework on the exact computation of the average capacity of multihop transmission, some examples are accentuated for generalized Nakagami-m fading channels. Numerical and simulation results, performed to verify the correctness of the proposed formulation, are in perfect agreement.
21st Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC) -- SEP 26-30, 2010 -- Istanbul, TURKEY
Keywords: Average capacity; multihop transmission; amplify-and-forward; relay technology; Meijer's G and Fox's H functions